Journal Economics, business & accountancy: EXPORT AND INVESTMENT IN FISHERIES SECTOR IN MALUKU PROVINCE - Yerimias Manuhutu (PPPM Perbanas, 2011)
Export and investment are considered important parts of the macro variables that affect economicgrowth. The purpose of this study in long-term perspective is to analyze the dynamicbehavior of export and investment and the movement direction of causality between exportsand investment in the province of Maluku. Data used in this research is secondary data, theperiod of 1990-2009. Estimation methods used in this study is Granger Causality Test, VectorAutoregressive (VAR).